THE NEGATIVE IMPACT OF SOCIAL AND MASS MEDIA ON PEOPLE’S BEHAVIORS AS REFLECTED IN HARVEY KAHN’S GIRL FIGHT - PUSPANINGRUM, GALUH WURI (Jurnal Ilmiah Mahasiswa FIB, 2013)
Keywords: media, mass media, social media, Facebook, Youtube, Socio-    Psychology, behavior.   Media were created to fulfill people’s need of communication and information. The variety of media in this modern era makes people consider media as one of their primary need especially in their social lives. Mass media are used as tools to gain information and social media  to communicate each other. This study aims to find the impact of media on people’s behaviors in film entitled Girl Fight (2011). Socio-psychological approach is used since this study is not only tries to find the impact of media in individual behavior, but people’s behaviors as a part of a society. The writer analyzes mass and social media’ impact and focuses on its negative influence towards people’s behaviors. Facebook and Youtube are kinds of social media which used as two ways communication and have negative influence pertain to the offensive statements or contents while the mass media television is use to shape public opinion.  Based on the data that are collected from the film, the writer finds many evidences pertain to media’s negative impact in characters’ behaviors. The offensive statements that are posts on Facebook become the reason for people to hate each other. People upload videos which contain violence and pornography on Youtube. Television as mass media in this film is not only depicted as a tool to shape public opinion, but also to gain popularity. For the future study, the writer suggests to analyze the impact of media to people’s behaviors not only in negative ways, but also the positive side of media’s impact. The analysis of media’s positive impact to  people’s behaviors will contribute deeper analysis for media influence towards people’s behaviors.